Analysis of Quality Control of Raw Materials with the Seven Tools Method on Sweet Bread Products at UD. Sarigut Bakery in Banda Aceh - Zia Ulhaq; Dewi Mulyati; Dini Fahlevi; Maulinda Maulinda (International Conference on Multidisciplinary Research, 2022)
Product quality is an important factor that affects the level of development and progress of a company. Companies that operate without paying attention to the quality of their products are tantamount to losing hope for the future of the company. The resulting product must always be checked for compliance with the established standards, so that the damage that occurs to the product can be reduced and eliminated. This study aims to analyze the quality control of raw materials using the seven tools method on sweet bread products at UD. Sarigut Bakery Banda Aceh. This research data is primary data obtained by researchers from questions posed to original sources and also observations of researchers at the location directly. The results of the study found that the quality control of raw and supporting materials was not good enough because the company was not able to maintain the quality standards and brands of materials set by using non-standard materials with lower quality levels. As for the feasibility of the storage warehouse, the control is quite good because the arrangement and placement of materials is orderly and the cleanliness of the warehouse and factory is quite well maintained. Disability caused by working hours is R² = 0.1336 or 13.36%. Defects due to long storage of raw materials are R² = 0.7254 or 72.54%. Meanwhile, defects due to the use of non-standard wheat flour raw materials are R² = 0.8621 or 86.21%. Non-standard raw materials are the biggest factor in causing product defects, this is caused by the condition of substitute materials that are not up to standard, which results in high water content in bread. Keywords: Quality control of raw materials, seven tools, sweet bread